Multi-hole gasoline direct injection:In-nozzle flow and primary breakup investigated in transparent nozzlesand with X-ray. (January 2018) - Bornschlegel, Sebastian; Conrad, Chris; Durst, Alexander; Wang, Jin; Wensing, Michael
The contribution describes the flow field inside modern gasoline direct-injection nozzles and sprays. Starting from the internal nozzle flow, results from transparent real-size nozzles are shown, where a significant vapor fraction even for cold fuel conditions is proven. Based on vapor fraction inside the nozzle, evidence for (super-)sonic flow conditions inside the nozzle is shown. The nozzle outlet velocity is determined by means of X-ray structure tracking velocimetry, which is a very powerful measurement technique to gain access to the very dense spray at the nozzle outlet. The X-ray velocities are compared to values that are determined by means of optical—phase Doppler anemometry/laser Doppler anemometry and Schlieren imaging—measurement techniques. By extrapolating the maximum droplet velocities found by laser Doppler anemometry in the more downstream regions of the spray to the nozzle outlet region, very similar velocities to the one derived from the X-ray measurements close to Bernoulli velocity are evaluated for typical gasoline direct-injection engine conditions. A third access to the nozzle outlet velocity is given by the derivation of penetration curves. The combination of vapor fractions and outlet velocities provides a measure for the initial spray momentum.